2004
DOI: 10.5005/jcdp-5-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Medical Health and Medication Use in Elderly Dental Patients

Abstract: The objectives of this study were to obtain information on the medical conditions and medications used among elderly Thai dental patients and to investigate the relationship between the findings in relation to age and sex. The information regarding medical conditions and medication use was obtained from interviews of 510 dental patients aged 60 years and older. The incidence of medical conditions was 82.5%; women had a significantly higher incidence of medical conditions (86.5%) than men (76.5%). The incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
32
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 28 publications
13
32
1
1
Order By: Relevance
“…The most common concomitant diseases were hypertension and diabetes mellitus. Our previous study in elderly dental patients showed a higher prevalence of hypertension (26.1%) than the prevalence (14.9%) reported in our TN sample 25 . Katusic et al.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The most common concomitant diseases were hypertension and diabetes mellitus. Our previous study in elderly dental patients showed a higher prevalence of hypertension (26.1%) than the prevalence (14.9%) reported in our TN sample 25 . Katusic et al.…”
Section: Discussioncontrasting
confidence: 51%
“…Our previous study in elderly dental patients showed a higher prevalence of hypertension (26.1%) than the prevalence (14.9%) reported in our TN sample. 25 Katusic et al 15 stated the only risk factors which have been clearly identified with TN are multiple sclerosis and hypertension. Recently, Teruel et al 17 studied the incidence of hypertension in their patients with TN and reported that the increased incidence of hypertension was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The average number of drugs used in that study was reported as 1.5 per person. 7 In our study, 386 patients (37 percent) were sixty years of age or older, and the average medication used in that age group was 1.5. Table 3 shows the common medications reported by our patients in this study.…”
Section: Discussionmentioning
confidence: 63%
“…In one study, 65.5% of dental patients older than 60 years were taking medication (17). A third of these patients were being treated for cardiovascular diseases, and hypertension was the most prominent condition (17). This further confirms the need for including cardiovascular diseases and drug interactions in dental curriculum.…”
Section: Discussionmentioning
confidence: 92%